2018
DOI: 10.5559/di.27.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early Retirement Intentions in Croatia

Abstract: In this paper, we use the SHARE (Survey of Health, Ageing and Retirement in Europe) Wave 6 dataset to look into the socio-demographic, health, well-being, financial and work--related predictors of intended early retirement in Croatia. We estimate logit regression models. Based on our research, early retirement seems to be more appealing to people who work in the private sector, who have poor quality of life, who are less educated, or report poor health status. Amending the pension system in terms of making ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Yet, Hofäcker, Schröder, Li, and Flynn's () study found lower‐educated people who were working in physically demanding jobs were more at risk of involuntary early retirement, as they needed to be physically able to work. This finding was consistent with a Canadian study (Scott et al, ) and also a Croatian study (Bađun & Smolić, ), which both found workers with lower educational levels were more likely to retire early.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Yet, Hofäcker, Schröder, Li, and Flynn's () study found lower‐educated people who were working in physically demanding jobs were more at risk of involuntary early retirement, as they needed to be physically able to work. This finding was consistent with a Canadian study (Scott et al, ) and also a Croatian study (Bađun & Smolić, ), which both found workers with lower educational levels were more likely to retire early.…”
Section: Resultssupporting
confidence: 91%
“…The most common factor identified for early retirement was ill health, with ill health associated with people not being able to work or with people having difficulty in performing as expected at work. For instance, ill health was found to be the main cause of early retirement in the Netherlands (de Wind et al, ), as well as a larger Europe‐based study (Axelrad, ), and a Croatian study (Bađun & Smolić, ). Consistently, in a Canadian study by Scott et al (), workers who sustained soft tissue injuries and permanent physical impairments were found to retire early (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…The low and middle income classes of Norway are stimulated by the tax system for early retirement (Hernoes et al 2000) and for males it is caused by low autonomy in their job as well (Blekesaune, Solem 2005). In Croatia, the reasons for early retirement are employment in the private sector, low quality of life, lower education and deteriorating health (Badun, Smolic 2018). Topa et al (2018) point to the importance of reasons for early retirement such as the timing of the employer's pension, organizational pressure, financial security, deteriorating health.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Our regression models are not weighted, but we account for clustering at the household level. It is important to recognize that our observations are not independent because research shows that partners tend to coordinate their work/retirement decisions (Gustman and Steinmeier, 2001;Ozawa and Lum, 2005;Bađun and Smolić, 2018).…”
Section: Modelsmentioning
confidence: 99%
“…The ageing of the population, compounding the decline in total population, is shrinking the available workforce and manifesting in the form of major labour shortages in Croatia (European Commission, 2019). Therefore, older workers' labour market transitions, and (early) retirement decisions especially (see Bađun and Smolić, 2018), have become an important, if not a central matter of public debate.…”
Section: Introductionmentioning
confidence: 99%